Oxidative DNA Damage-induced PARP-1-mediated Autophagic Flux Disruption Contributes to Bupivacaine-induced Neurotoxicity During Pregnancy - Luo, Jiaming; Zeng, Lei; Li, Ji; Xu, Shiyuan; Zhao, Wei (Current Neuropharmacology, 2023)
Objective: Severe neurologic complications after spinal anesthesia are rare but highly distressing, especially in pregnant women. Bupivacaine is widely used in spinal anesthesia, but its neurotoxic effects have gained attention. Methods: Furthermore, the etiology of bupivacaine-mediated neurotoxicity in obstetric patients remains unclear. Female C57BL/6 mice were intrathecally injected with 0.75% bupivacaine on the 18th day of pregnancy. We used immunohistochemistry to examine DNA damage after bupivacaine treatment in pregnant mice and measured γ-H2AX (Ser139) and 8-OHdG in the spinal cord. A PARP-1 inhibitor (PJ34) and autophagy inhibitor (3-MA) were administered with bupivacaine in pregnant mice. Parp-1flox/flox mice were crossed with Nes-Cre transgenic mice to obtain neuronal conditional knockdown mice. Then, LC3B and P62 staining were performed to evaluate autophagic flux in the spinal cords of pregnant wild-type (WT) and Parp-1-/- mice. We performed transmission electron microscopy (TEM) to evaluate autophagosomes. Results: The present study showed that oxidative stress-mediated DNA damage and neuronal injury were increased after bupivacaine treatment in the spinal cords of pregnant mice. Moreover, PARP-1 was significantly activated, and autophagic flux was disrupted. Further studies revealed that PARP-1 knockdown and autophagy inhibitors could alleviate bupivacaine-mediated neurotoxicity in pregnant mice. Conclusion: Bupivacaine may cause neuronal DNA damage and PARP-1 activation in pregnant mice. PARP-1 further obstructed autophagic flux and ultimately led to neurotoxicity.
Keywords: pregnancy